2009
DOI: 10.1074/jbc.m809058200
|View full text |Cite
|
Sign up to set email alerts
|

G Protein Mono-ubiquitination by the Rsp5 Ubiquitin Ligase

Abstract: Emerging evidence suggests that ubiquitination serves as a protein trafficking signal in addition to its well characterized role in promoting protein degradation. The yeast G protein ␣ subunit Gpa1 represents a rare example of a protein that undergoes both mono-and poly-ubiquitination. Whereas mono-ubiquitinated Gpa1 is targeted to the vacuole, poly-ubiquitinated Gpa1 is directed instead to the proteasome. Here we investigate the structural requirements for mono-and poly-ubiquitination of Gpa1. We find that va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 63 publications
1
30
0
Order By: Relevance
“…Third, Rsp5 is capable of ubiquitinating Ste4 in vitro. Notably, earlier studies showed that Rsp5 is also responsible for the ubiquitination of Ste2 (receptor) (44) and the monoubiquitination (but not the polyubiquitination) of Gpa1 (G␣) (43). Thus, Ste4 joins a growing list of signaling proteins that serve as substrates of Rsp5.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Third, Rsp5 is capable of ubiquitinating Ste4 in vitro. Notably, earlier studies showed that Rsp5 is also responsible for the ubiquitination of Ste2 (receptor) (44) and the monoubiquitination (but not the polyubiquitination) of Gpa1 (G␣) (43). Thus, Ste4 joins a growing list of signaling proteins that serve as substrates of Rsp5.…”
Section: Discussionmentioning
confidence: 99%
“…This is in marked contrast with both Ste2 and Gpa1. In both cases, ubiquitination by Rsp5 serves to target the proteins for internalization and eventual degradation in the vacuole (43,44).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the UD functions as a site of phosphorylation, polyubiquitination (for targeting to the proteasome), and monoubiquitination (for trafficking to the vacuole) (25, 26, 28 -31). Gpa1 is monoubiquitinated by the Rsp5 ubiquitin ligase (26). However, the proteins involved in Gpa1 endocytosis and specifically those that recognize monoubiquitin within the UD are not known.…”
Section: Structural Contributions Of the Ubiquitination Domain Tomentioning
confidence: 99%
“…In contrast to Ste2, monoubiquitination of Gpa1 is not dependent on pheromone stimulation. Both proteins are monoubiquitinated by the same ubiquitin ligase, Rsp5 (26,27).…”
mentioning
confidence: 99%